Analisis Karakteristik Daya Saing Regional Kasus Kabupaten/Kota Pulau Jawa Tahun 2003 - Susanti, Ira (UI Scholars Hub, 2008)
Competitiveness is a crucial factor in regional development process. The more open region of technology and information, the more competitive that region in regional competition. Because nowadays, competition not only between nations but also between regions. The purpose of regional competitiveness description is to analyze how technology and innovation have important role in productivity and also social welfare. This regional competitiveness will be explained by Regional Competitiveness Index that following Huggins Regional competitiveness model.